Estratégia para obtenção de sólidos multicomponentes de insumos farmacêuticos ativos - Oliveira, Alcemira Conceição (2013)
This study deals with strategies for rational designing of multicomponent solids emtricitabine, and a salt ondansetron hydrochloride based on crystal engineering and polymorphism of efavirenz. The efavienz is a Non-Nucleoside Reverse Transcriptase Inhibitors (NNRTI) with low solubility. In this case, it was investigated the influence of the preparation method of efavirenz (Form I) using a solvent-assisted milling method which induces indeed the formation of a polymorphic form (form III). These results suggested that the described method produces the polymorph III as well as a small amount of a solvated metastable form. The solvate form latter changes into form III under room temperature and pressure conditions in the presence of atmospheric humidity. It was also observed that the form III was two times more soluble than form I. In this sense the form III could be a viable option to be considered in developing new formulations. The adopted strategies combined functional groups of the active pharmaceutical ingredients to obtain supramolecular targets by intermolecular hydrogen bonds. Two classes of drugs, a Non-Nucleoside Reverse Transcriptase Inhibitors (NNRTI), emtricitabine, and a salt ondansetron hydrochloride were studied in this perspective. The salt is responsible for controlling the side effect induced by cytotoxic chemotherapy and radiotherapy treatments. The screening strategies to obtain multicomponent solids were based on Cambridge (CSD) database. In case of emtricitabine, 86% of the reported structures interact by intermolecular hydrogen bonds between the fragments fluorocytosine and the carboxylic groups. For ondansetron hydrochloride salt, 13% of the reported structures exhibit intermolecular bonds between the imidazole and carboxyl group mediated by the ion chloride. Based on these results, seven multicomponent solids forms of emtricitabine with carboxylic acid were successfully synthesized. Whereas three multicomponent solids for the ondansetron hydrochloride salt with two carboxylic acids and one amino acid containing carboxyl groups in its molecular structure were observed. The multicomponent solids were obtained through slurry and mechanochemical procedures. The physico-chemical characterizations were performed by Fourier Transform (infrared and Raman) vibrational spectroscopy measurements, powder X-ray diffraction, crystallographic analysis and Thermogravimetric and Differential Scanning Calorimetry thermal analysis.